Innovativeness, absorptive capacity and innovation among Malaysian micro-enterprises: a cross-industry and cross-state comparison - Abdullah Al- Mamun; Rajennd Muniady; Noorshella Che Nawi; Malarvizhi. C.A; P. Yukthamarani Permarupan (American Scientific Publishers, 2017)
The objective of this study is to determine the distribution of micro-entrepreneur’s innovativeness, micro-enterprise innovation, and absorptive capacity of micro-enterprises across industries and states of Peninsular Malaysia. Innovativeness and absorptive capacity are considered key factors affecting the performance of enterprises. This study employs the cross-sectional approach and quantitative data were collected through structured interviews from 417 women micro-entrepreneurs in Peninsular Malaysia. Findings of this study show that the distribution of micro-enterprise innovativeness and absorptive capacity of micro-enterprises is significantly different across the states of Malaysia. Policy makers should therefore focus on increasing participation in the national innovation system, public institutes and universities, and encourage commercialization and research and development activities, and technological uptake in order to increase the micro-enterprise innovativeness and absorptive capacity of micro-enterprises in the states with low levels of innovativeness and absorptive capacity, as it is expected to affect enterprise performance and national economic development.